Intellectual Property Rights in BRICS Countries: Legal Frameworks, Enforcement Challenges, and Economic Implications - Haryono Haryono; Woro Utari; Diah Ayu Rahmawati; Budi Endarto; Bagus Teguh Santoso (Westscience Press, 2024)
This study explores the legal frameworks, enforcement challenges, and economic implications of Intellectual Property Rights (IPR) in BRICS countries—Brazil, Russia, India, China, and South Africa—using a normative juridical approach and qualitative analysis. The findings reveal significant disparities in the governance of IPR among these nations, with China and India leading in innovation and enforcement reforms, while Brazil, Russia, and South Africa face persistent challenges related to institutional capacity and judicial delays. Despite progress in aligning with international standards such as TRIPS, enforcement gaps and socio-economic priorities influence the effectiveness of IPR systems. The study also highlights the dual economic impact of IPR: fostering innovation and investment while raising concerns over access to essential goods. This research underscores the need for harmonized frameworks, enhanced enforcement mechanisms, and a balanced approach to innovation and equity in BRICS countries.